DINAMIKA POPULASI DAN LAJU EKSPLOITASI CUMI-CUMI (Sepioteuthis Lessoniana) DI KEPULAUAN SPERMONDE SULAWESI SELATAN - Ernaningsih Aras; Muhammad Jamal Alwi; Nur Indah (JURNAL AKUAKULTUR, TEKNOLOGI DAN MANAJEMEN PERIKANAN TANGKAP, ILMU KELAUTAN, 2019)
Squid Sepioteuthis lessoniana is a sought-after fisheries commodity, leading to a high exploitation rate. This affects the sustainability of Squid (S. lessoniana) resources in wild, especially Spermonde Island. The aim of this study was to determine the population dynamics and the exploitation rate of Squid (S. lessoniana) in the Spermonde Islands of South Sulawesi. The results of the study are expected to provide information on the level of utilization of Squid and as a basis for sustainable management of squid in Spermonde Islands. The present study was conducted from March to July 2019 in Spermonde Islands, South Sulawesi. A survey was performed by direct measurement of the fish captured by local fishermen and merchants. Data collected on length and weight of squid were carried out for 3 or 4 times a week. The results showed length of squid ranged from 06 to 28 cm, the relationship between the length of the weight was negative allometric, the age group consisted of 4, the growth rate (K) of 0.37 per year, the maximum length (L max) of 31.5 cm, the total mortality rate (Z) of 2.85 per year, the natural mortality rate (M) of 0.95 per year, the capture mortality rate (F) of 1.90 per year and the exploitation rate is classified into over-exploitation.